Passion in sport: a systematic review in the context of individual modalities (Research, Society and Development, 2020)
The aim of this study was to conduct a systematic review of the literature on studies involving passion and individual sports. The searches were led by Scopus, Sport Discus, PubMed, PsycINFO, Science Direct, Scielo, Lilacs and Web of Science databases. The data were analyzed by the content analysis technique of the categorical type. The review included 18 studies published in the period of 2009 to 2018, with a quantitative (94.4%) and qualitative (5.6%) character to investigate the passion in the sports context. The age of the participants ranged from 12 to 81 years and the majority of the samples were composed of 100 to 300 athletes (76.5%), being a large part of the studies performed with both sexes (88.8%) and most researches developed in Europe (50%). The results revealed a greater number of studies associating negative characteristics with obsessive passion, such as fear of failure and negative affection, besides being associated with low global self-esteem, burnout and stress. Regards to harmonious passion, positive associations with positive affect, athletic identity and sports performance were observed. It was concluded that the passion related to individual sports is associated with positive and negative psychological factors, so that the predominance of these factors depends on the form of internalization of the passion in the identity of the subject, presenting beneficial effects or not to its performance and other activities performed.